2019
DOI: 10.3390/app9050998
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Wind Energy Harvesting Using Passive Turbulence Control Devices

Abstract: Aiming to predict the performance of galloping piezoelectric energy harvesters, a theoretical model is established and verified by experiments. The relative error between the model and experimental results is 5.3%. In addition, the present model is used to study the AC output characteristics of the piezoelectric energy harvesting system under passive turbulence control (PTC), and the influence of load resistance on the critical wind speed, displacement, and output power under both strong and weak coupling are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…23) Baghaee et al suggested a new solution based on Lagrange multipliers for an aeroelastic panel flutter analysis of rectangular composite plates sandwiched between two MFCs. 24) Enhancing wind energy harvesting using a passive turbulence control device was experimentally verified by Wang et al 25) Therefore, it is considered that the MFC has significant potential for practical applications in small-scale flutter energy harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…23) Baghaee et al suggested a new solution based on Lagrange multipliers for an aeroelastic panel flutter analysis of rectangular composite plates sandwiched between two MFCs. 24) Enhancing wind energy harvesting using a passive turbulence control device was experimentally verified by Wang et al 25) Therefore, it is considered that the MFC has significant potential for practical applications in small-scale flutter energy harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…Within the huge range of nonlinear EH systems, there are some particular themes of note; natural single-potential nonlinearities (classical continuous nonlinear systems like the Van-der-Pol or Duffing oscillator, a pendulum, etc. as in [16][17][18][19][20][21][22]), natural or imposed geometrical nonlinearities (systems with double, triple or multiple stable equilibriums, as in [23][24][25][26][27][28][29][30]), systems with a nonlinear interaction such as flow-induced vibration systems (see [31][32][33][34][35] and references therein), and systems with strongly nonlinear or discontinuous nonlinearities like dry friction, piecewise discontinuity or vibroimpacts [36,37]. It has been shown that the nonlinear mechanisms for EH are far more beneficial than linear ones.…”
Section: Introductionmentioning
confidence: 99%
“…The galloping has a larger amplitude and a wider vibration frequency band than the VIV, and is generally considered to be a vibration of a single mode, which provides a more effective guarantee for stable acquisition of energy [26]. The structure of the circular cross section does not gallop, because for a circular cross-section, if no vortex shedding occurs, no lift will occur [27]. When the cylinder is vibrating perpendicular to the direction of the fluid, the force of the fluid is consistent with the direction of the relative flow velocity, and the component in the direction of the structural vibration is opposite to the direction of motion of the structure.…”
Section: Introductionmentioning
confidence: 99%